The Case Method in Islamic Education as an Effort to Strengthen Students’ Character Values: A Literature Review - Ushwa Dwi Masrurah Arifin Bando (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
This study explores the development of Islamic character values through the implementation of a case method–based learning model in Islamic Religious Education (PAI) at the university level. The research highlights three fundamental pillars of character formation: curricular learning, the establishment of a religious campus culture, and character reinforcement through co-curricular activities. Within the curricular aspect, character values are integrated through systematic instructional planning, including syllabus development, course design, and the use of Islamic civilization materials as contextual learning resources. The study also emphasizes the strategic role of the campus mosque as a practical learning space and cultural symbol that represents the integration of Islamic teachings with Indonesian local culture. The case method enables meaningful learning experiences by engaging students in problem-solving activities grounded in real socio-religious issues and by encouraging the examination of scriptural evidence within contemporary contexts. Digital learning media, interactive multimedia, and authentic assessment techniques—such as observation, self-assessment, peer assessment, worship journals, and interviews—are utilized comprehensively in the evaluation process. The findings indicate that this approach effectively enhances students’ religious literacy, critical thinking abilities, and social character, particularly in responding to the challenges of the disruption era. In conclusion, the case method–based PAI learning design offers a progressive, humanistic, and value-oriented pedagogical framework that contributes significantly to the revitalization of Islamic education management. This approach not only strengthens students’ abilities in problem-solving and religious practice but also provides a strategic foundation for advancing character education in higher education institutions.